PROPOSITION OF A METHODOLOGY FOR MAPPING AND MODELING PROCESSES FOR HIGHER EDUCATION INSTITUTIONS - Barros, Fernando Rufino de; Paes, Julianna Cunha; Garnier, Natacha Rohen Christo; Nogueira, Rodrigo Tavares; Morais, Alline Sardinha Cordeiro (Revista Valore, 2023)
This article aims to present the development of a methodology, and its artifacts, for the application of the Business Process Management (BPM) approach within the administrative unit of the Federal Institute of Education, Science and Technology Fluminense. The work proposal is to identify, prioritize and model processes "as is", guiding decision making and facilitating communication and cooperation, serving as a link between organizational strategies and the daily activities performed by the institution’s servers. To achieve the proposed objective, action-research was adopted, carried out between 2019 and 2020, and a structure was built based on the BPM cycle, with the adapted use of the GUT matrix, 5W1H technique, Business Process Management Notation, Tangible Business Process Management, and Bizagi Modeler software. As a contribution, a methodology of great relevance was defined for its easy adaptation to institutional needs, proving to be applicable to other public educational institutions. The study innovated by presenting the set of instruments used and validated in the different sectors of the Rectory of IFFluminense, regardless of their purpose or organization.